Quantitative phase recovery in ghost imaging - Singh R.K.; Vinu R.V.; Chen Z.; Pu J. (My University, 2025)
We discuss a novel technique for the simultaneous recovery of quantitative phase and amplitude information of a complex-valued object in ghost imaging by adopting the concepts of holography in combination with the ghost diffraction scheme. The applicability of the approach is experimentally demonstrated with quantitative imaging for various pure phase objects, planar transparencies, etc. © 2021 IEEE.